Attitudes toward the use of ChatGPT to seek oncological information: a qualitative study - Durosini, Ilaria; Masiero, Marianna Agnese; Strika, Milija; Mazzoni, Davide; Pravettoni, Gabriella (Frontiers in Psychology, 2025)
IntroductionThe rapid diffusion of new technologies and Artificial Intelligence is revolutionizing access to information for patients with different diagnoses. The spread of ChatGPT, an OpenAI-developed tool that utilizes the GPT language model technology to generate human-like responses based on human questions, also influences how information can be acquired. In this era of technological improvements, it is important to explore people's attitudes toward the use of AI. The main aim of this study is to explore people's attitudes related to using ChatGPT to obtain new information regarding oncological diagnosis through a qualitative data collection.MethodAfter reading an ad hoc scenario with an example of a conversation between ChatGPT and a hypothetical user who received an oncological diagnosis, participants were invited to complete online open questions.ResultsA thematic analysis and a Word Association Analysis were conducted on the data collected on 74 Italian participants, revealing both positive and negative emotions. Participants recognized that the use of ChatGPT could help to speed up times and to provide updated information, improving the understanding of complex medical terms. However, concerns about possible negative consequences related to an incorrect use of ChatGPT emerged from the data, in addition to difficulties in understanding the process of data elaboration or data privacy, and the impossibility of replacing the human-doctor relationship.DiscussionThe study underscores the necessity of implementing robust security measures and clear protocols to address concerns and enhance the trustworthiness of ChatGPT in medical contexts, helping the promotion of a safe and correct use of these technologies.